Monkeypox infection and bacterial cellulitis: a complication to look for - De Sousa, Diogo (2022)
© 2022 The Authors. Published by Elsevier Ltd on behalf of International Society for Infectious Diseases. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)